Information Technology-Based Administration System at SMP Boarding School Al-Muayyad Sidoarjo - Eka Putra Romadona; Muhammad Thohir; Aba Agil Aziz (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to describe the administrative system applied at SMP Boarding School al-Muayyad by utilizing technology to make it easier for teachers to record and assess students. This research is field research with a qualitative descriptive approach. This study took place at the Al-Muayyad Boarding School Junior High School. Sources of data in this study are the results of interviews, observations, and documentation. The analytical technique used by the researcher is descriptive qualitative. The results of this study are an information technology-based administrative system that is applied at the Al-Muayyad Boarding School Junior High School including forms, advantages, and disadvantages in the technology-based administrative process. This research also provides an overview of how to create and process code-based applications. These results offer codular optimization as an aid for institutions to facilitate the creation of an Android-based administrative system. Thus, it is hoped that there will be more formal institutions that can use codular as a tool to facilitate the implementation of the administrative system in their schools.